TRANSITION OFFENSE IN TOP-LEVEL EUROPEAN BASKETBALL - Mario Jeličić, (Sport Scientific And Practical Aspects, 2025)
Purpose: The purpose of this study was to determine differences in the use of transition pick and roll/pop and transition post-up maneuvers in two top teams from the EuroLeague basketball (first placed and ninth placed teams in the 2019/2020 season). Methods. The sample of respondents consisted of 56 EuroLeague basketball games played by teams Anadolu Efes Istanbul (28) and Zalgiris Kaunas (28), the ANA team and the ZALAG team respectively. Variables for estimating transition offenses were collected during EuroLeague senior basketball matches. A total of 16 variables (Toff_tot, TP&R/P_tot, TP&R/P_suc, TP&R/P_uns, %suc P&R/P, %uns P&R/P, TP_up_tot, TP_up_suc, P_up_uns, %suc P_up, %uns_ P_up, TO, % TO, Toff_point, TP&R/P_point; and Tpup_point) were assessed to estimate transitional offenses in teams that use early pick and post-up maneuvers in their performance. Results. Findings showed statistically significant differences between two analyzed teams in variables as described further in the text. The ANA team performed less TP & R/P_tot offenses per game then the ZALG team. Also, when it comes to the total number of transition post-up situations, the ANA performed less of these then the ZALG per game. At the end, the ANA team lost on average less balls than the ZALG team per game in the Transition offense. Conclusions. Obtained differences that occurred between two analyzed basketball teams cannot fully explain placement of the teams in the table. The main difference comes from the philosophy of the coach and the very concept of the team or individual quality of the players.